Prevalensi Miopia pada Mahasiswa FKIK UKRIDA Angkatan 2019 dan Hubungannya dengan Pembelajaran Daring selama Masa Pandemi - Putri, Dhenisa Eka Kurnia (Jurnal MedScientiae, 2024)
Myopia is a common vision condition in which a person can see nearby objects clearly, but objects further away are blurry. In Indonesia, the prevalence of refractive errors ranks first, covering 25% of the population or around 55 million people. In December 2019, the novel coronavirus spread rapidly in China and around the world. Social restriction and regional quarantine policies have the potential to limit people from carrying out activities, especially in educational institutions. Purpose: to determine the prevalence of myopia sufferers and their relationship with online learning. Methods: using a total sampling technique with a cross sectional method with 162 respondents. Results: It was found that respondents who used devices for a duration of <4 hours and a distance of <30 cm tended not to experience myopia (P>0.05). By looking at the results obtained through the Chi-Square test, it can be concluded that there is no relationship between online learning and myopia. Conclusion: it can be concluded that there is no relationship between online learning and myopia in active students of FKIK UKRIDA class of 2019 and the prevalence of myopia in active students of FKIK Ukrida class of 2019 is 60.1%.